2018
DOI: 10.1111/opn.12213
|View full text |Cite
|
Sign up to set email alerts
|

Being acknowledged by others and bracketing negative thoughts and feelings: Frail older people's narrations of how existential loneliness is eased

Abstract: Aims and objectives The aim of this study was to describe how EL was eased, as narrated by frail older people. Background Existential loneliness (EL) is an unavoidable part of the human condition. It is a complex phenomenon that has been described as disconnection from life. If EL is acknowledged in the care of older people, the experience of EL can be reduced. Design In this qualitative study, we used an exploratory and descriptive design. Methods The study was based on 22 narrative interviews with frail olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 32 publications
6
40
0
3
Order By: Relevance
“…Their narratives conveyed a felt gap between meaningless life they now experienced and the sense of 'fullness' they craved in the past. These experiences are consistent with EL arising from an emptiness and disconnected with actual life of the frail elderly, advanced cancer patients, dying persons and terminally ill patients [37][38][39]. However, unlike Kitzmüller et al (2018) review, both Chinese and Swedish older adults in our study made the distinction of "overcoming" rather than "being trapped", (whether the older adults were male or female), though they also depicted EL as a devasting condition connected with negative emotions (i.e., hopelessness, losses, meaningless, see no purpose in life and no value in continuing to live [36].…”
Section: Discussionsupporting
confidence: 76%
“…Their narratives conveyed a felt gap between meaningless life they now experienced and the sense of 'fullness' they craved in the past. These experiences are consistent with EL arising from an emptiness and disconnected with actual life of the frail elderly, advanced cancer patients, dying persons and terminally ill patients [37][38][39]. However, unlike Kitzmüller et al (2018) review, both Chinese and Swedish older adults in our study made the distinction of "overcoming" rather than "being trapped", (whether the older adults were male or female), though they also depicted EL as a devasting condition connected with negative emotions (i.e., hopelessness, losses, meaningless, see no purpose in life and no value in continuing to live [36].…”
Section: Discussionsupporting
confidence: 76%
“…Specifically, loneliness is defined as subjective distress resulting from a discrepancy between desired and actual relationships (Ernst & Cacioppo, 1999), while social isolation is the objective lack of social contacts and interactions (Cornwell & Waite, 2009;Gardner, Brooke, Ozanne, & Kendig, 1999). Loneliness may be modifiable, and person-focused interventions are an important but underdeveloped approach (Perissinotto, Holt-Lunstad, Periyakoil, & Covinsky, 2019) Several published papers have focused on the qualitative experience of loneliness among overseas or immigrant populations (Wong, Chau, Fang, & Woo, 2017), medically ill persons (Drageset, Eide, Dysvik, Furnes, & Hauge, 2015;Sj€ oberg, Edberg, Rasmussen, & Beck, 2019), and people at highest risk for loneliness (Neves, Sanders, & Kokanovi c, 2019). However, there is little published literature on qualitative studies of loneliness among independent living older adults in the community.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research in home healthcare has indicated challenges related to communication as well as ethical concerns (Choe et al, ; Sundler, Eide, Dulmen, & Holmström, ). Some challenges are related to older persons’ autonomy and fragility, as well as to existential concerns and emotional needs (Fjordside & Morville, ; Sjöberg, Edberg, Rasmussen, & Beck, ). Additionally, older persons may express their emotions and needs vaguely, and as such, they can be difficult to detect (Sundler et al, ).…”
Section: Introductionmentioning
confidence: 99%